HUBUNGAN KERJA DALAM INDUSTRI FAST FASHION: ANALISIS ISI TERHADAP FENOMENA EKSPLOITASI (STUDI KASUS FILM THE TRUE COST DAN NIKE SWEATSHOPS) - Apriliani, Tri (Universitas Negeri Yogyakarta, 2016)
The fast-fashion industry is one of the manufacturing industry that is associated with the developing countries as a producer of their products. Authors carriying an issue of labor relations in the fast-fashion industry which is very important to be studied due to exploitation issues. The main focus of the study is to assess the film